Percepção de editores brasileiros da Ciência da Informação sobre critérios Qualis Periódicos - Felix, Victória Lopes (2021)
Presents historical and concepts about scholarly communication, with a focus on scientific journals fro m its birth, to the Brazilian journals in the area of Librarianship and Information Science. Highlights the Coordination for the Improvement of Higher Level Personnel (CAPES) and its relevance in the development and consolidation of postgraduate programs in Brazil. It addresses the emergence of Qualis Journals, the criteria and benchmarks used from 1998 onwards, the assessments in the field of Communication and Information, in addition to the proposed criteria for the 2017-2020 evaluation. Research is characterized as descriptive, bibliographic, and documentary, with a quantitative and qualitative approach, as well as content analysis. As a question of the research problem, we ask, what is the view of the editors of the journals in the area of Information Science, about the Qualis-journals evaluation criteria? From that question, we set the following general objective: Analyze the Qualis Journals criteria from the viewpoint of editors in the area of Information Science. This goal has evolved into the following specific objectives: to map out the Brazilian Journals in the area of Information Science; Characterize these editors; Understand editor’s perception of Qualis Journals criteria and parameters. In order to find out the views of the publishers, a questionnaire was applied consisting of open and closed questions. Out of the 46 total questionnaires applied, we obtained a 67.4% response rate from publishers. It concluds that editors display polarized vision: some say they favor the changes to Qualis Journals, others are dissatisfied with the requirements of cri teria such as internationalization, indexing in foreign databases, the obligation of foreign members on the editorial committee and articles with international authorship.